Pengaruh Pendidikan Kesehatan terhadap Pengetahun Ibu Hamil Tentang Skrining Hipotiroid Kongenital (SHK) di Puskesmas Pulisan Sulawesi Utara - Meilanny G.H Warouw; Rifzul Maulina (Jurnal Siti Rufaidah, 2025)
Congenital hypothyroidism is a condition of decreased or non-functioning thyroid gland that is present since newborns. This occurs due to anatomical abnormalities or metabolic disorders of thyroid hormone formation or iodine deficiency. Congenital Hypothyroidism Screening (CHS) is an important health program that aims to detect thyroid disorders early in newborns. Congenital Hypothyroidism Screening is a screening/screening test to sort out babies suffering from Congenital Hypothyroidism from babies who do not suffer. This study aims to determine the effect of health education on pregnant women's knowledge about congenital hypothyroidism screening (CHS). This study used a Pre-Experimental Design with a One Group Pre-test and Post-test Design. The sample consisted of 56 pregnant women with sampling using a purposive sampling technique. Data collection was carried out by questionnaire and analyzed using the Wilcoxon Test. The results of the study obtained that most of the respondents' knowledge before being given the intervention was in the sufficient category (42.9%). While most of the knowledge after being given the intervention was in the good category (78.6%). The Wilcoxon test yielded a p-value of 0.00 < 0.05, indicating an effect of health education on knowledge about congenital hypothyroidism (CHS) screening among pregnant women at the Pulisan Community Health Center. This study is expected to provide input to pregnant women, who should be more critical, especially regarding indicators of understanding, examination timing, and the impact of not undergoing CHS. They can frequently read the KIA book and leaflets provided during counseling sessions to gain better and more quality knowledge.